Acúmulo de carboidratos no desenvolvimento de tomateiro tratado com produtos químicos - Pereira Ramos, Anamaria Ribeiro [UNESP] (2015)
This work had the purpose to study the physiological effects of pyraclostrobin, boscalid, plant growth regulators and plant extract on the accumulation of carbohydrates during the development of tomato plants (Solanum lycopersicum L.), hybrid Giuliana, in protected environment conditions. The treatments were: T1- control; T2- pyraclostrobin 0.2 g L-1; T3- boscalid 0.075 g L-1, T4- pyraclostrobin 0.2 g L-1 + boscalid 0.075 g L-1, T5- IBA + GA(3) + kinetin 375 mg L-1, T6- GA(4+7) + benzylaminopurine 100 mg L-1 and T7- plant extract 100 mg L-1. The carbohydrate accumulation curve was accomplished with 5 samples, at 20-day intervals between evaluations, the 1st evaluation being carried out at 30 days after transplantation, on the day of the first treatment application. At each sampling the plants were separated in stem, leaves and fruits, of which the contents of total soluble sugars, reducing sugars and saccharose were evaluated. The effects of the treatments on chlorophyll content and gas exchanges were also evaluated. The experimental design was completely randomized, with 4 repetitions and 6 destructive evaluations during the development, with 1 plant per experimental unit for each sampling. The pyraclostrobin and boscalid applied in isolation and/or combined favor the increase of carbohydrates in leaves, stems and fruits of tomato hybrid Giuliana.